2019
DOI: 10.1007/978-3-030-29888-3_11
|View full text |Cite
|
Sign up to set email alerts
|

A Fractal-Based Approach to Network Characterization Applied to Texture Analysis

Abstract: This work proposes a new method for texture analysis that combines fractal descriptors and complex network modeling. At first, the texture image is modeled as a network. Then, the network is converted into a surface where the Cartesian coordinates and the vertex degree is mapped into a 3D point in the surface. Then, we calculate a description vector of this surface using a method inspired by the Bouligand-Minkowski technique for estimating the fractal dimension of a surface. Specifically, the descriptor corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This is a classic line of research in the Scientific Computing Group where many texture recognition methods have been developed in the last decade. (16,19,131,154,(199)(200)(201)(202)(203)(204)(205)(206)(207) We discussed this approach in more detail in Chapter 2, Section 2.3.3.1. Here, we describe a new method focusing on one of the latest developments of the approach, (19) where a multilayer network is built for trichromatic (RGB) images.…”
Section: Spatio-spectral Network (Ssn)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is a classic line of research in the Scientific Computing Group where many texture recognition methods have been developed in the last decade. (16,19,131,154,(199)(200)(201)(202)(203)(204)(205)(206)(207) We discussed this approach in more detail in Chapter 2, Section 2.3.3.1. Here, we describe a new method focusing on one of the latest developments of the approach, (19) where a multilayer network is built for trichromatic (RGB) images.…”
Section: Spatio-spectral Network (Ssn)mentioning
confidence: 99%
“…32 SEM images were acquired with scales 200 nm and 300 nm, corresponding to sensing units that were subjected to distinct concentrations of PCA3 in addition to the negative sequence (non-complementary) and a blank measurement for control. Afterwards, they are rescaled to 1024 × 768 pixels and cropped using different window sizes (50,100,200,300,400, and 500 pixels), with no overlap. We empirically found that the window size of 300 × 300 pixels was the best approach for training the models (results with other crop dimensions can be consulted in (242)), so we consider this in the following.…”
Section: Image Acquisitionmentioning
confidence: 99%